2016
DOI: 10.4269/ajtmh.16-0033
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Gold Standard Testing for Diagnosing Leptospirosis: Further Evidence from a Well-Characterized, Flood-Related Outbreak in Sri Lanka

Abstract: Abstract. A gap in the leptospirosis field remains the lack of well-characterized sample collections that allow for comparison of new methods to standard ones. In the context of a flood-related outbreak of leptospirosis evaluated in Anuradhapura, Sri Lanka, a specimen bank was obtained with detailed metadata accompanied by gold standard diagnostic test results. Blood samples collected on admission and 14 days later from suspected cases of leptospirosis were tested using microscopic agglutination test (MAT) (17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…Validity was assessed for most techniques compared to MAT. Although MAT was once considered the gold standard, it is no longer considered as such for various reasons [9]. Further, many studies from Sri Lanka used MAT, which was performed using the genus-specific Patoc strain without having a broad panel of serovars or regionally optimized serovars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validity was assessed for most techniques compared to MAT. Although MAT was once considered the gold standard, it is no longer considered as such for various reasons [9]. Further, many studies from Sri Lanka used MAT, which was performed using the genus-specific Patoc strain without having a broad panel of serovars or regionally optimized serovars.…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis mimics dengue, hantavirus, malaria, rickettsioses and viral sepsis [7, 8] which can cause delayed diagnosis and increased mortality. Although the microscopic agglutination test (MAT) was considered “standard” for diagnosing leptospirosis [9], it is no longer considered the “gold standard” due to its well documented low sensitivity and predictive values [9, 10]. Lack of point of care diagnostic facility severely affect the leptospirosis diagnosis; hence, the global disease estimates may not be entirely valid for country level estimates.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinically suspected cases of leptospirosis without laboratory confirmation, 3-HADH was detected in 10% of the cases. A recent study by Agampodi et al., showed that due to the lack of seroconversion in some patients, paired-sample MAT negative cases were positive with a more sensitive such as qPCR [19] . We were not able to detect leptospiral DNA in the MAT-negative/3-HADH-positive cases, however, because a negative PCR in a symptomatic patient will not rule out the diagnosis of leptospirosis, further study is needed to conclude if our antiserum is cross–reacting with a host protein.…”
Section: Discussionmentioning
confidence: 99%
“…17 Conversely, molecular testing methods using PCR have been demonstrated to be more effective in the acute phase. 18 Similarly, antigen-based detection methods such as the Dual Path Platform assay have been shown to be highly sensitive in the acute setting of severe disease and show promise for rapid detection in a broad range of healthcare settings. 19 Future clinical-based studies should evaluate the prospect of Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%